Incidencia del Clima Organizacional en el Desempeño Laboral del personal de la Importadora Megafiestas, junio 2024. - Palacios López, Lizbeth Katherine (2024)
This research work was get done at “Importadora Megafiestas”, and the general objective was to determine how the organizational environment affects the work performance of the company's employees. The following questions were set out: How does the organizational environment affect the work performance of the company “Importadora Megafiestas”, measured as two groups of variables which have subgroups of variables (dimensions)?; How do the individual variables of the organizational environment group affect the performance of the personnel? According to the methodology was developed with qualitative and quantitative, descriptive and inferential research, using inferential statistical models; and, as for the quantitative analysis of the data, was applied a survey as a tool for 40 workers of the company. Besides, Microsoft Excel complements were used both for the description of data and for the correlation of variables, among other tools. In addition, were used statistical functions to determine the degree of dependence that exists between them. The present research topic was focused on measuring the incidence of the organizational climate on work performance, for this purpose, it was established as a null hypothesis, that in the importer “Megafiestas” there is an incidence of the organizational environment on work performance and as an alternative hypothesis, the organizational environment variable does not affect the work performance variable. Finally, in the results of the analysis was determined a weak incidence (0.018), reviewed the quantitative analysis using the above mentioned tools, and it was found that in the case of "Importadora Megafiestas” the organizational environment is not affecting the work performance, therefore, the null hypothesis is rejected and the alternative hypothesis is accepted